2015
DOI: 10.7314/apjcp.2015.16.17.7959
|View full text |Cite
|
Sign up to set email alerts
|

Serum Anti-Gal-3 Autoantibody is a Predictive Marker of the Efficacy of Platinum-Based Chemotherapy against Pulmonary Adenocarcinoma

Abstract: Background: Identification of predictive markers for the efficacy of platinum-based chemotherapy is necessary to improve the quality of the life of cancer patients. Materials and Methods: We detected proteins recognized by autoantibodies in pretreated sera from patients with lung adenocarcinoma (AC) evaluated as showing progressive disease (PD) or a partial response (PR) after cisplatin-based chemotherapy by proteomic analysis. Then, the levels of the candidate autoantibodies in the pretreated serum were valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In addition, GAL3 induces chemoresistance by regulating apoptotic activity through phosphorylation and translocation of GAL3, regulation of mitochondrial membrane potential, and regulation of cell survival and caspase pathways 15 . Further, we previously reported that serum anti‐GAL3 autoantibody levels effectively predicted the efficacy of platinum‐based chemotherapy for advanced NSCLC 16 . However, no study has investigated the efficacy of GAL3 as a predictor of AC efficacy in patients with resected NSCLC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, GAL3 induces chemoresistance by regulating apoptotic activity through phosphorylation and translocation of GAL3, regulation of mitochondrial membrane potential, and regulation of cell survival and caspase pathways 15 . Further, we previously reported that serum anti‐GAL3 autoantibody levels effectively predicted the efficacy of platinum‐based chemotherapy for advanced NSCLC 16 . However, no study has investigated the efficacy of GAL3 as a predictor of AC efficacy in patients with resected NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…15 Further, we previously reported that serum anti-GAL3 autoantibody levels effectively predicted the efficacy of platinumbased chemotherapy for advanced NSCLC. 16 However, no study has investigated the efficacy of GAL3 as a predictor of AC efficacy in patients with resected NSCLC. Therefore, this study aimed to analyze the association of GAL3 expression with the clinicopathological characteristics and prognosis of patients with surgically resected stages II and IIIA NSCLC and administered adjuvant chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…The titles and abstracts of 7173 articles were screened and a total of 7079 were excluded based on the exclusion criteria described above. Of the remaining 94 full-text articles, 10 were excluded because a disease control was used 1423 , 9 were excluded because they did not have satisfied outcomes 24–32 , and 8 were excluded because of their small sample size ( n < 10) 3340 , Ultimately, 67 articles were included in this systematic review evaluating the diagnostic performance of TAAbs in serum or plasma for LC detection (Tables 1 and 2).…”
Section: Study Identification and Literature Searchmentioning
confidence: 99%
“…Anti-AFP, -Gankyrin, -GPC-3, -IMP1, -p62, -Koc, -p53, -c-Myc, -Cyclin-B1, -HuD, -Survivin, -MAGEA4, -p16, -SOX-2, -CAGE, -NY-ESO-1, -GBU4-5 of autoantibodies against galectin-3 could be useful to predict the efficacy of chemotherapy in patients with lung adenocarcinoma (230).…”
Section: Role Of Autoantibodies To Self Antigens As Biomarkers For Camentioning
confidence: 99%